Laparoscopic liver resection with open partial resection of the thoracoabdominal wall for cancer along the transhepatic biliary drainage tract: A case report. (November 2021) - Tsukamoto, Tadashi; Kodai, Shintaro; Tajima, Tetsuzo; Kanazawa, Akishige; Takahama, Makoto; Mikami, Shinichi
Abstract: Introduction and importance: Recently, laparoscopic liver resection has been established as a standard procedure for a certain group of hepatic resections; its indications and procedures have been expanding. Case presentation: A 67-year-old woman was referred with a chief complaint of left subcostal pain. Eight years and nine months before, she underwent pancreatoduodenectomy for cancer of the ampulla of Vater after endoscopic retrograde biliary drainage for obstructive jaundice. A trans-anastomotic internal-external retrograde transhepatic biliary drainage (RTBD) catheter was placed intraoperatively. Based on radiological findings, intrahepatic cholangiocarcinoma, or local recurrence of cancer of the ampulla of Vater, invading the anterior thoracoabdominal wall, diaphragm, and pericardium, without distant metastasis, were considered. Laparoscopic lateral segmentectomy of the liver combined with open en bloc resection of the invaded portion of the anterior thoracoabdominal wall with costal cartilage, diaphragm, and pericardium was performed. The postoperative course was uneventful, and the patient was discharged 17 days post-surgery. The patient died of cancer recurrence 46 months later. Clinical discussion: The cancer invaded along the RTBD tract. Although the mechanisms of carcinogenesis remain unclear, transhepatic biliary drainage is a risk factor for cancer invasion along the tract. Laparoscopic liver resection before open thoracoabdominal wall resection ensured clear delineation of the cancer margins invading the thoracoabdominal wall and minimized the defect of the thoracoabdominal wall. Conclusion: Laparoscopic liver resection for hepatic cancer invading adjacent structures or organs would be feasible and useful in selected patients, even if resection of the invaded area is performed by open surgery. Highlights: Cancer developed along the retrograde transhepatic biliary drainage tract after pancreatoduodenectomy. Laparoscopic liver resection and simultaneous open en bloc partial resection of the thoracoabdominal wall was performed. The patient's 46-month survival post-operation was relatively long for recurrent cancer of the ampulla of Vater.